Diabetes mellitus after injury in burn and non-burned patients: A population based retrospective cohort study - Duke, J.; Randall, S.; Fear, M.; Boyd, James; Rea, S.; Wood, F. (Pergamon Press, 2018)
© 2017 Elsevier Ltd and ISBI. Objective: To compare hospitalisations for diabetes mellitus (DM) after injury experienced by burn patients, non-burn trauma patients and people with no record of injury admission, adjusting for socio-demographic, health and injury factors. Methods: Linked hospital and death data for a burn patient cohort (n = 30,997) in Western Australia during the period 1980-2012 and two age and gender frequency matched comparison cohorts: non-burn trauma patients (n = 28,647); non-injured people (n = 123,399). The number of DM admissions and length of stay were used as outcome measures. Multivariate negative binomial regression was used to derive adjusted incidence rate ratios and 95% confidence intervals (IRR, 95%CI) for overall post-injury DM admission rates. Multivariate Cox regression models and hazard ratios (HR) were used to examine time to first DM admission and incident admission rates after injury discharge. Results: The burn cohort (IRR, 95%: 2.21, 1.80-2.72) and other non-burn trauma cohort (IRR, 95%CI: 1.63, 1.24-2.14) experienced significantly higher post-discharge admission rates for DM than non-injured people. Compared with the non-burn trauma cohort, the burn cohort experienced a higher rate of post-discharge DM admissions (IRR, 95%CI: 1.40, 1.07-1.84). First-time DM admissions were significantly higher during first 5-years after-injury for the burn cohort compared with the non-burn trauma cohort (HR, 95%CI: 2.00, 1.31-3.05) and non-injured cohort (HR, 95%CI: 1.96, 1.46-2.64); no difference was found > 5. years (burn vs. non-burn trauma: HR, 95%CI: 0.88, 0.70-1.12; burn vs non-injured: 95%CI: 1.08 0.82-1.41). No significant difference was found when comparing the non-burn trauma and non-injured cohorts (0-5 years: HR, 95%CI: 1.03, 0.71-1.48; > 5years: HR. 95%CI: 1.11, 0.93-1.33). Conclusions: Burn and non-burn trauma patients experienced elevated rates of DM admissions after injury compared to the non-injured cohort over the duration of the study. While burn patients were at increased risk of incident DM admissions during the first 5-years after the injury this was not the case for non-burn trauma patients. Sub-group analyses showed elevated risk in both adult and pediatric patients in the burn and non-burn trauma. Detailed clinical data are required to help understand the underlying pathogenic pathways triggered by burn and non-burn trauma. This study identified treatment needs for patients after burn and non-burn trauma for a prolonged period after discharge.